Do minimal interventions increase participation rates in voluntary online training at high school? - Beek, Sophie van der; Bellhäuser, Henrik; Hertel, Silke (Psychology learning & teaching, 2021)
In preparation for graduating from high school, students face the challenge of having to learn the subject matter of several school years with little guidance. The ability to self-regulate learning is conducive to this. Research has shown that students’ self-regulated learning can be successfully promoted through training. However, when such training is provided voluntarily, not all students participate and dropout rates tend to be high. Minimal interventions on utility value and implementation intention are promising approaches to increase the use of voluntary training. This study investigates whether short interventions can increase the participation in voluntary self-regulated learning training and whether differences in participation can be explained by motivation profiles. A randomized intervention study was conducted with 269 students assigned to one of four conditions: utility value, implementation intention, a combination of utility value and implementation intention, or a control condition. Regression analyses show the minimal interventions on utility value and implementation intention had no effect on training participation. Positive predictors, however, were expectancy for success and mean grade score. In addition, latent profile analyses showed a three-class model with the profiles “motivated,” “balanced,” and “unmotivated.” Motivated students participated in the training significantly more often than students with other profiles. Implications for theory development and practice are discussed.
"First published online October 15, 2020".- Artikel-Frontdoor
Gesehen am 09.09.2024